English pronunciation errors among Jordanian university students: The phonotactic, motivation and attitude factors - Naser, Issa Mohammad Muflih (2023)
This study aimed at identifying pronunciation difficulties among Jordanian English as a Foreign Language (EFL) students examining the roles of phonotactic structures, motivation and attitude. In addition, it aimed at examining the moderating role of motivation on the relationship between EFL students’ attitudes and intelligible pronunciation. The study employed a mixed-methods research design implementing qualitative and quantitative methods. Based on a random sampling technique, 257 Jordanian EFL students responded to the questionnaire. Audio recording and interviews were also conducted with 16 Jordanian EFL students selected purposively. Findings indicated that EFL students’ motivation has a significant relationship with EFL intelligible pronunciation; while EFL students’ attitudes have no significant relationship. However, it is found that motivation of EFL students’ significantly moderates the relationship between EFL students’ attitudes and intelligible pronunciation. Interview findings complemented questionnaires’ findings and indicated that motivation moderates this relationship. Besides, interview findings concluded that students’ perceptions of pronunciation difficulties are mostly related to socio-psycho factors. They also indicated strong motivation can enhance pronunciation intelligibility and change their attitudes to acquire intelligibility. Additionally, the interview indicated that multimedia were main strategies of enhancing intelligible pronunciation. Audio recording found that students of EFL in Jordan still face a challenge of syllable structure. Additionally; they pronounce unintelligibly /p/ and /ε/ sounds indicating that the position of /p/ sound is essential, more specifically, the medial and final positions of /p/ being more problematic. In addition, /ε/ sound is more difficult when it is preceded by voiceless sound. These findings offer several implications for EFL teachers and policy makers which could prove beneficial for Jordanian EFL students’ intelligible pronunciation in terms of increasing EFL students’ attitudes and enhancing the role of motivation to acquire intelligible pronunciation.